2006
DOI: 10.1021/bi0519001
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine 90 and 93 Are Localized within the Phenol Binding Site of Human UDP-Glucuronosyltransferase 1A10 as Determined by Photoaffinity Labeling, Mass Spectrometry, and Site-Directed Mutagenesis

Abstract: 4-Azido-2-hydroxybenzoic acid (4-AzHBA), a novel photoactive benzoic acid derivative, has been synthesized and used as a photoprobe to identify the phenol binding site of UDP-glucuronosyltransferases (UGTs). Analysis of recombinant His-tag UGTs from the 1A family for their ability to glucuronidate p-nitrophenol (pNP) and 4-methylumbelliferone (4-MU) revealed that UGT1A10 shows high activity toward phenols and phenol derivatives. Purified UGT1A10 was photolabeled with 4-AzHBA, digested with trypsin, and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 52 publications
7
44
0
Order By: Relevance
“…Similarly, in the human sulfotransferase SULT1A1, substrate inhibition by dopamine was observed when Phe-247 was mutated to leucine and was interpreted to mean that this substitution created space for the binding of a second dopamine molecule (35). Finally, the UDPglucuronosyltransferase human UGT1A10 has an amino acid motif ( 90 FMVF 93 ) that is postulated to be involved in binding of its phenolic substrates through ring stacking with the phenylalanine residues (38). Three mutants, V92A, F93G, and F93A, all show substrate inhibition kinetics (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the human sulfotransferase SULT1A1, substrate inhibition by dopamine was observed when Phe-247 was mutated to leucine and was interpreted to mean that this substitution created space for the binding of a second dopamine molecule (35). Finally, the UDPglucuronosyltransferase human UGT1A10 has an amino acid motif ( 90 FMVF 93 ) that is postulated to be involved in binding of its phenolic substrates through ring stacking with the phenylalanine residues (38). Three mutants, V92A, F93G, and F93A, all show substrate inhibition kinetics (36).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the large number of biotransformation reactions mediated by UGTs, relatively little is known about the critical amino acids involved in the direct interactions of these enzymes with naturally occurring substrates, drugs, or environmental pollutants. In our previous report, the two phenylalanine residues of the F 90 -M 91 -V 92 -F 93 motif located within the N-terminal domain of UGT1A10 were identified as being critical to the binding and glucuronidation of simple phenols [23]. This motif was identified using photoaffinity labeling followed by LCMS/ MS sequencing and site-directed mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This motif was identified using photoaffinity labeling followed by LCMS/ MS sequencing and site-directed mutagenesis. In those studies, two mutations of this motif, F90A and F93A, were generated and evaluated with two specific phenolic compounds, 4-nitrophenol and 4-methylumbelliferone [23]. The current study was undertaken to further clarify the role of the previously identified FMVF motif of UGT1A10, and analysis of the two previously generated mutants as well as 3 new mutants, F90L, F93L, and V92A, revealed that the two amino acids, F 90 and F 93 , are also critical for the glucuronidation of native estrogens and their hydroxylated derivatives, while V 92 only decreases the activity of this enzyme toward E 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations